Peningkatan Kemampuan Pemahaman Matematis Siswa Kelas V Pada Pembelajaran Kooperatif Tipe Think Pair Share - Ervin Reliavirli Rusti (Journal of Contemporary Issue in Elementary Education, 2023)
The ability to understand is the main requirement in the process of learning mathematics. Understanding is the basis for achieving the expected abilities in mathematics. This study aims to obtain an overview of the increase in the ability to understand mathematically geometric material (cubes and blocks) in students who receive cooperative learning with the think-pair-share type and direct learning. The method in this study was a quasi-experimental design using non-equivalent groups for pretest and posttest. The subjects of this study were two classes, namely the fifth grade at an elementary school in Cidahu, Sukabumi Regency, West Java Province. From this study, it was concluded that, based on the average increase in students' mathematical understanding abilities in geometric material (cubes and blocks), those who studied with the think pair and share type cooperative model achieved higher results than those who received direct learning.